Psychological distress and its associated factors in health workers during COVID-19 pandemic in Nepal: An online survey - Shrestha, Nirmala; Gurung, Nisha; Banstola, Sanju; Sah, Saurabh Kishor; Koirala, Sharad; Sharma, Bimala (Journal of Gandaki Medical College-Nepal, 2021)
Introduction: Psychological distress among healthcare workers amidst COVID-19 pandemic has emerged as a serious health problem. Understanding its magnitude is crucial to guide policies and interventions to improve their psychological wellbeing. This study assessed the psychological distress and its associated factors among health care workers in Nepal during the COVID-19 pandemic.Methods: A cross-sectional online survey was carried out among 427 health workers currently working in Nepal from April 25 to June 10, 2020. Psychological distress was measured using “The Kessler Psychological Distress Scale” (K10). Descriptive statistics and inferential statistics were computed at a 5% level of significance. Ethical approval was taken from Nepal Health Research Council.Results: A total of 427 healthcare workers participated in the study. Out of the total participants, 50.4% were males. Nearly half of the participants were medical doctors (48%) followed by nurses (22.2%), health assistants (12.2%) and 61% were non-government employees. The healthcare workers who experienced symptoms of psychological distress were 28.9%. Out of 123 respondents who had symptoms of psychological distress, 19% had mild, 7.3% had moderate and 2.6% had severe psychological distress. Female healthcare workers were more likely to have psychological distress than males [AOR: 1.75, CI: 1.05-2.92].Conclusions: Psychological distress in healthcare workers during the COVID-19 pandemic is a matter of serious health concern. This issue demands urgent comprehensive intervention embracing the provision of a supportive environment and protective equipment, screening psychological outcomes and psychological counseling especially targeting female healthcare workers.